Encyclopedia of Robotics 2018
DOI: 10.1007/978-3-642-41610-1_50-1
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Underwater Snake Robots

Abstract: Abstract-Increasing efficiency by improving the locomotion methods is a key issue for underwater robots. Hence, an accurate dynamic model is important for both controller design and efficient locomotion methods. This paper presents a model of the kinematics and dynamics of a planar, underwater snake robot aimed at control design. Fluid contact forces and torques are modeled using analytical fluid dynamics. The model is derived in a closed form and can be utilized in modern model-based control schemes. The prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
75
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(75 citation statements)
references
References 23 publications
0
75
0
Order By: Relevance
“…In [1], [12], for a neutrally buoyant USR considering that the fluid is viscid, incompressible, and irrotational in the inertia frame and that the current is constant and irrotational in the inertial frame, it is shown that the fluid forces on all links can be expressed in vector form as…”
Section: Hydrodynamic Modelingmentioning
confidence: 99%
See 3 more Smart Citations
“…In [1], [12], for a neutrally buoyant USR considering that the fluid is viscid, incompressible, and irrotational in the inertia frame and that the current is constant and irrotational in the inertial frame, it is shown that the fluid forces on all links can be expressed in vector form as…”
Section: Hydrodynamic Modelingmentioning
confidence: 99%
“…There are several models proposed for swimming snake-like robots. A discussion of the different modeling approaches proposed for USRs can be found in [5], [12]. This paper proposes a closed form model for USRs swimming in a 2D plane, which takes into account the extra propulsion forces acting along the body when the snake robot is equipped with different added effectors, such as a caudal tail, fins, stern propeller, and tunnel thrusters, in addition to the propulsion forces generated by the link angle motion together with the hydrodynamic forces.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, a number of snake-like robots can achieve diverse locomotion, for instance, serpentine forward [2], roll to the sideways [3], climb along poles, and swim under water [4]. However, none of those snake-like robots can achieve autonomous locomotion, i.e., the capabilities to autonomously decide how, when, and where to move.…”
Section: Introductionmentioning
confidence: 99%